Traumatic impact of Tran Mong Tu in her poem “The Gift in Wartime” - Gurung, Raj Kumar (Pursuits: A Journal of English Studies, 2023)
This study surveyed the traumatic impacts of Tran Mong Tu in her poem, “The Gift in Wartime”. The poem is related to the Vietnam War (1954-1975) survivors and Tu’s trauma. As Tu’s husband’s death traumatized her and she expressed her frustration and tension in the poem, several other war victims were traumatized. Her trauma represented the Vietnam War survivors. This research attempted to find out the cathartic release of war veterans' traumatic impacts. She behaved like an abnormal person. She offered her husband roses and tears on his grave. The findings of the study showed that one of the best therapies or cathartic release of traumatic impacts was to forget it, compromise it and purge it. Transformation and purgation are the best ways to release the trauma. The study focuses on realizing the fact and being satisfied by adjusting to the situation. Trauma has not been studied yet from this angle. Crying might be the most common ways of outlet of cathartic release. Releasing the trauma depends on the individual’s tackling and compromise. Writing is the best way of releasing the trauma although listening to music also lessens it. Tu attempted to release her traumatic pain through her poems. She suffered psychologically from post-traumatic stress disorder (PTSD). This study employed the trauma theory to analyze the poem.